The Experience with Biosimilars of Infliximab in Rheumatic Diseases - Azevedo, Valderilio F.; Kos, Igor Age; Ariello, Leonardo (Current Pharmaceutical Design, 2017)
Background: Infliximab biosimilars are the first biosimilars of monoclonal antibodies approved by the main regulatory agencies. Up to the present day, two infliximab biosimilars have been approved: CT-P13 (Celltrion), and SB2 (Biogen), but other companies have been developing candidate infliximab biosimilars that are on clinical trials: PF 06438179 (Pfizer), the ABP710 (bioCentury/Amgen) the BCD055 (JSC Biocad Russica) and BOW015 (Epirus). Methods: We have made a literature search in MedLine database using the key words [Infliximab] and [biosimilars] and [rheumatic diseases] and [rheumatisms]. We have also made a search in the clinicaltrials.org website. Conclusions: Clinical data published so far have provided important evidence on long-term efficacy and safety, immunogenicity and switching, supporting the use of CT-P13 and SB2 for the treatment of rheumatic diseases. In addition, the European experience has proved the economic advantages of the incorporation of infliximab biosimilars in clinical practice. Despite the widespread use of infliximab biosimilars there is still a lack of data regarding interchangeability between reference products and biosimilars.
Keywords: immunogenicity